Utilization of Agricultural Waste for the Cultivation of Pleurotus Mushrooms in Thailand - Nattawut Rungjindamai; Kittipong Trakunjarunkit; Thanutcha Posalee; Duangkamol Limpanya (My University, 2024)
Thailand is one of the major agricultural production countries in the world. Therefore, large amounts of agricultural waste are generated as by-products of the agroindustry. The wastes are usually discarded or burnt, resulting in environmental pollution. The main goal of this research was to evaluate the use of agricultural waste for mushroom cultivation. A total of 15 mushroom isolates were recovered from mother spawns and basidiocarps. They were screened for their cellulolytic enzyme activity on Czapek agar using carboxymethyl cellulose (CMC) as the sole carbon source. Two isolates of the oyster mushrooms, Pleurotus pulmonarius PP6 and Pleurotus ostreatus PO3, produced the best enzyme activities. To observe the mycelial growth on agricultural waste, the two oyster mushroom candidates were cultured in jars containing five different types of agricultural waste: corn husk, rice straw, coconut meal, coconut husk and sugarcane bagasse, and the jars were incubated at 25°C for six weeks. The results show that both isolates grew best on coconut meal, producing very densely packed mycelia. Meanwhile, corn husk and rice straw were also good sources for oyster mushroom cultivation. This study shows that these three substrates have the potential to be utilized in mushroom cultivation on a commercial scale.
Keywords: Husk; Pleurotus; Pleurotus ostreatus; Bagasse; Edible mushroom; Fungal Biology and Applications